Prediger der Demokratie Die Deutsche Hochschule für Politik und die politische Bildung in West-Berlin (1949-1972/74) - Ludwig, Felix (Schriften des Bundesarchivs, Sonderreihe "Die zentralen deutschen Behörden und der Nationalsozialismus", 2023)
After the end of National Socialism, the young West German political science saw itself as the vanguard of German democratization. In West Berlin in particular, political scientists such as Ernst Fraenkel, Ossip Flechtheim and Otto Heinrich von der Gablentz were especially enthusiastic at the German School of Politics. They saw themselves as "preachers of democracy" in postwar Germany. This study examines how these actors transferred their pluralistic theories of democracy into practical political education. Thus, at the intersection of the history of ideas, institutions, and biographies, it contributes to the question of how West German democracy succeeded after 1945.